University Students’ Ability to Interpret Visual Representations in Plant Anatomy - Susiyawati, Enny (Curtin University, 2017)
This case study investigated first year university students’ ability to interpret visual representations—micrographs—in plant anatomy following instruction. Quantitative and qualitative data were collected through diagnostic tests, lesson observations, interviews, and document reviews. The findings revealed that students’ difficulties when interpreting plant micrographs was due to insufficient conceptual understanding and inadequate skills in reasoning and identification. A greater focus on these skills should support students’ ability to interpret visual representations in plant anatomy.